ANTIOXIDANT, ANTIBACTERIAL AND ANTIBIOFILM POTENTIALS OF ANISE (Pimpinella anisum) SEEDS EXTRACTED ESSENTIAL OILS - Al- wendawi, SH. A.; Gharb, L. A.; Al ghrery, R. S. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
Anise (Pimpinella anisum) is an annual herbaceous flowering plant, its widely used as spices, flavoring agent and fragrance. Anise seeds and its essential oils (EOs) has been used widely in the recipes of folk medicine in the Arab region, including Iraq. Therefore, the goal of this work was to extract and define the chemical compositions of aniseeds EOs, and study its antioxidant, antibacterial, and antibiofilm potentials. Aniseed EOs were extracted by hydro-distillation technique using Clevenger apparatus. Twenty-five distinct compounds have been recognized by Gas chromatographic–Mass spectral (GC-Mas) analysis, the major constituents were anisole (87.99%) followed by estragole (3.01%), and all other components were presented in less than 2%. The aniseed EOs showed potent antioxidant activity for scavenging of 2,2 diphenyl - 1-picrylhydrazyl (DPPH) in concentrations-dependent manner, the highest antioxidant (84.9±0.267%) was recorded at 10000 ppm. Antibacterial activity regards to minimum inhibitory concentration (MIC) against burn wounds isolated Pseudomonas aeruginosa were of the rang 4000-7000ppm. Aniseed EOs revealed excellent antibiofilm activity against P. aeruginosa biofilms formation with reduction percentage ranged from 26 - 86.41% in co-treatment assay, while the inhibition potentials for pre-developed biofilm decreased significantly (P